2020
DOI: 10.3390/nu12103175
|View full text |Cite
|
Sign up to set email alerts
|

St. John’s Wort Suppresses Growth in Triple-Negative Breast Cancer Cell Line MDA-MB-231 by Inducing Prodeath Autophagy and Apoptosis

Abstract: The rational regulation of programmed cell death by means of autophagy and apoptosis has been considered a potential treatment strategy for cancer. We demonstrated the inhibitory effect of St. John’s Wort (SJW) on growth in the triple-negative breast cancer (TNBC) cell line and xenografted mice and its target mechanism concerning autophagic and apoptotic cell death. SJW ethanol extract (SJWE) inhibited proliferation in a dose-dependent manner. SJWE treatment dramatically increased autophagy flux and apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The cultured metabolic-imbalanced neurons at DIV 6 were treated with exendin-4 for 24 h. Protein levels and phosphorylation were analyzed using western blot analysis. An earlier study revealed that HFD induces insulin resistance through dephosphorylation of IRS-1 at tyrosine 612, AKT at serine 473, glycogen-synthase kinase-3beta (GSK-3β) at serine 9 in the brain 31 . In the present metabolic imbalanced model, it induced a similar dephosphorylation of IRS-1, AKT, GSK-3β in primary hippocampal and cortical neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The cultured metabolic-imbalanced neurons at DIV 6 were treated with exendin-4 for 24 h. Protein levels and phosphorylation were analyzed using western blot analysis. An earlier study revealed that HFD induces insulin resistance through dephosphorylation of IRS-1 at tyrosine 612, AKT at serine 473, glycogen-synthase kinase-3beta (GSK-3β) at serine 9 in the brain 31 . In the present metabolic imbalanced model, it induced a similar dephosphorylation of IRS-1, AKT, GSK-3β in primary hippocampal and cortical neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…St. John’s Wort was also found to induce autophagy and apoptosis in MDA-MB-231 cells [ 42 ]. Anti-apoptotic proteins were downregulated and the p-PI3K/PI3K and p-mTOR/mTOR ratios were also suppressed.…”
Section: Resultsmentioning
confidence: 99%
“…When autophagy was suppressed with 3-MA, cell proliferation increased and rates of apoptosis reversed, indicating that St. John’s Wort may work on the pro-death autophagy pathway. When studied in MDA-MG-231 xenografted athymic nude mice, administration of St. John’s Wort induced autophagy and apoptosis, as well as in vivo tumor growth inhibition [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…As we all know, autophagy is very important for the maintenance of homeostasis, and it is responsible for the elimination of damaged or redundant macromolecules such as proteins, damaged organelles, and lipids (White, Mehnert, & Chan, 2015). In addition, excessive autophagy induces autophagic cell death (ACD) through excessive self‐digestion and degradation of essential cellular components (You, Lee, Kim, Kook, & Kim, 2020). Otherwise, some studies have shown that the regulation of autophagy can increase tumor cell sensitivity to chemotherapeutic agents (Santofimia‐Castaño & Iovanna, 2021; Tan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%